2002
DOI: 10.1097/01.asn.0000033275.17169.67
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Cell Volume and Nitric Oxide Concentration in Macula Densa Cells Caused by Changes in Luminal NaCl Concentration

Abstract: Abstract. The luminal NaCl concentration ([NaCl]) at the macula densa (MD) controls both tubuloglomerular feedback (TGF) and renin release. Nitric oxide (NO) inhibits TGF sensitivity to a great extent. The NO concentration in the MD cells is not known. This study measured this concentration in MD cells with confocal microscopy in the isolated perfused thick ascending limb using a NO-sensitive fluorophore 4,5-diaminofluorescein (DAF-2). Calcein was used to measure cell volume changes. The loop perfusion fluid w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
75
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 42 publications
4
75
1
Order By: Relevance
“…The simplest route to this end would be for NO formation to vary in proportion to physiologic changes in macula densa salt. The present findings call this into question, but one might reconcile these data, the opposite finding from Liu et al (7), and the micropuncture data from various labs (1,6) by making the reasonable supposition that there are sodium-dependent and sodium-independent pathways competing for control of NOS I in the macula densa and that circumstances can arise where one or the other dominates. In fact, we observed this in micropuncture experiments where NOS I activity was dominated by macula densa salt in normal rats, but not in rats with streptozotocin diabetes (unpublished observation).…”
supporting
confidence: 45%
See 1 more Smart Citation
“…The simplest route to this end would be for NO formation to vary in proportion to physiologic changes in macula densa salt. The present findings call this into question, but one might reconcile these data, the opposite finding from Liu et al (7), and the micropuncture data from various labs (1,6) by making the reasonable supposition that there are sodium-dependent and sodium-independent pathways competing for control of NOS I in the macula densa and that circumstances can arise where one or the other dominates. In fact, we observed this in micropuncture experiments where NOS I activity was dominated by macula densa salt in normal rats, but not in rats with streptozotocin diabetes (unpublished observation).…”
supporting
confidence: 45%
“…Kovacs et al (4) are the second group to measure the effect of macula densa salt on NO production. Recently, Liu et al (7) reported that macula densa NO is salt-dependent. Now, Kovacs et al (4) do likewise, with one critical caveat, namely that the salt stimulus required to elicit NO is supraphysiologic and may not be relevant to daily life.…”
mentioning
confidence: 99%
“…We, and others, have taken advantage of fluorescent probes that have been developed to measure NO levels. In our studies we monitored extracellular levels of NO using the fluorescent probe DAF-FM and found that increases in luminal [NaCl] resulted in the generation of NO by macula densa cells [63,73]. Further, we found that NO inhibited apical Na:2Cl:K cotransporter activity in macula densa cells.…”
Section: Modulators Of Tgf Produced By Macula Densa Cellsmentioning
confidence: 76%
“…It was shown recently by using ATP-sensitive reporter cells that MD cells release ATP and that this release is stimulated by raising NaCl concentration (8). Enhanced release of ATP may be related to the swelling of MD cells, which is another consequence of elevating luminal NaCl (21)(22)(23). It is likely that ecto-ATPases dephosphorylating ATP to AMP are present in cells adjacent to the MD.…”
Section: Figurementioning
confidence: 99%